Purgatory Ridge a Cork O'Connor mystery - Krueger, William Kent (New York : Pocket Books, 2001)
The 200 acres of great white pines, sacred to the Anishinaabe tribe and known to them as Minishoomisag (the native word for Our Grandfathers), lie just a stone's throw from the lumber mill of Karl Lindstrom, a wealthy industrialist hardly known for his environmental sensitivity. So, when an explosion at Lindstrom's mill results in the death of one of his night watchmen, it's little wonder that suspicion falls on the tribesmen. And for Cork O'Connor, a local man struggling to repair his life and his crumbling marriage, a criminal investigation and the evidence it yields will challenge his public duty and private concerns as never before.
106219
Keywords: O'Connor, Cork (Fictitious character) -- Fiction; Private investigators -- Minnesota -- Fiction; Ojibwa Indians -- Minnesota; Minnesota -- Fiction; Detective and mystery fiction; Fiction; Mystery fiction